(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
The criminal justice system should not only focus on identifying offenders, proving criminal acts, and imposing punishment, but also on preventing further harm to witnesses and victims. In Indonesia, witness and victim protection has developed from a limited procedural arrangement under the Criminal Procedure Code toward broader protection through sectoral statutes, Law No. 13 of 2006, Law No. 31 of 2014, and the more recent Law No. 3 of 2026 on Witness and Victim Protection. This study aims to analyse the development of witness and victim protection within the Indonesian criminal justice system and to formulate an integrated criminal law policy model for strengthening such protection. This research uses a normative juridical method with a qualitative orientation. The analysis is conducted through statutory, conceptual, historical, and legal policy approaches by examining primary legal materials and secondary legal literature related to victimology, criminal law, restitution, compensation, and victim recovery. The findings show that Indonesian law has gradually expanded the scope of protected subjects, strengthened the institutional role of the Witness and Victim Protection Agency, and introduced new mechanisms such as the Victim Endowment Fund, regional government support, and information technology-based coordination. However, the existing framework still faces fragmented protection standards, obstacles in restitution enforcement, weak inter-institutional coordination, and the need for more operational implementing regulations. This study contributes by offering an integrated protection model that connects risk assessment, witness security, victim recovery, restitution, compensation, institutional coordination, regional support, and secure information technology.